2012
DOI: 10.1177/1071181312561407
|View full text |Cite
|
Sign up to set email alerts
|

Combating Vigilance Decrements in a Sustained Attention Task: Lack of Support for the Utility of a Cognitive Intervention Secondary Task

Abstract: Results from previous studies (St. John & Risser, 2007, 2009) indicate the addition of a simple cognitive secondary task may mitigate vigilance decrements for a sustained attention task involving target acquisition. The effectiveness of the cognitive task increased when its onset was triggered by physiological indicators of inattention. The current study examined the generalizability of this methodology with a few modifications. A no intervention condition was added to provide a baseline and a short perceptual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In their review of 112 rail crashes and incidents occurring in Australia between 1990 and 1994, Edkins and Pollock found that the need for sustained attention was the most salient human factor contributing to all incident types, and particularly for skills-based errors involving the failure to monitor and correctly respond to railway signals ( 7 ). Results from vigilance studies indicate that the introduction of a cognitive secondary task may assist humans in sustaining levels of vigilance and task performance during a prolonged attention task ( 1113 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their review of 112 rail crashes and incidents occurring in Australia between 1990 and 1994, Edkins and Pollock found that the need for sustained attention was the most salient human factor contributing to all incident types, and particularly for skills-based errors involving the failure to monitor and correctly respond to railway signals ( 7 ). Results from vigilance studies indicate that the introduction of a cognitive secondary task may assist humans in sustaining levels of vigilance and task performance during a prolonged attention task ( 1113 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This can be explained by the consequences of sleepiness and mental fatigue on human performance. In fact, mental fatigue and sleepiness have important impacts on perception, attention, decision‐making, and judgment, and can lead to slower reaction times, misjudgments, and inferior detection of critical elements within one's environment (e.g., Carretta & French, 2012; Gunzelmann & Gluck, 2009; Guo et al, 2016; Lopez de la O et al, 2012; see Abd‐Elfattah et al, 2015, for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Hypovigilance is even associated with difficulties in takeover performance in automated driving situations (Jarosch et al, 2019; Matthews et al, 2019). The consequences of hypovigilance can also be observed in non‐driving domains such as command and control operations, i.e., occupations entailing providing key information and orders for security operations such as emergency management, police or firefighting operations, and surveillance (e.g., Carretta & French, 2012). In the last few decades, the role of human operators has constantly evolved with the emergence of automation, shifting toward systems supervision and the management of malfunctions and unusual events (Parasuraman, 1986; Sheridan, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the SSSQ, the DSSQ Worry factor appears more purely cognitive. Regardless of these differences, the SSSQ has been employed in studies investigating stress states in performance contexts (Carretta & French, 2012;Cottrell & Barton, 2012;Helton, Fields, & Thoreson, 2005;Pfaff, 2012;Pfaff & McNeese, 2010;Pirzadeh & Pfaff, 2012;Seidelman et al, 2010;Taylor & Barnett, 2010) and although there are slight differences in how the primary three factors are construed, the overall structure and results appear similar to the DSSQ. Helton's (2004) initial work on the SSSQ was presented, however, in an abbreviated format published in the proceedings of the Human Factors and Ergonomics Society.…”
mentioning
confidence: 99%